Analysis of Hydraulic Oil Replacement Intervals and Operating Temperature for Enhancing Hydraulic System Performance in Komatsu Excavator PC2000-11 - Chandra Ajik Prakoso; Muhamad Safi'i; Althesa Androva (JURUTERA - Jurnal Umum Teknik Terapan, 2026)
The performance of hydraulic systems in heavy equipment is influenced by hydraulic oil condition, particularly oil replacement intervals and operating temperature. This study aims to analyze the effect of these factors on the hydraulic system performance of a Komatsu PC2000-11 excavator. The research employed an experimental approach through oil analysis and operating temperature monitoring at intervals of 12,983; 13,473; 13,980; and 14,260 operating hours. Oil samples were analyzed using the Oil Spectrometric Analysis (OSA) method with parameters including viscosity, Total Acid Number (TAN), and wear metal content. The results showed that iron (Fe) wear metal concentration increased from 3 ppm to 31.3 ppm as operating hours increased, indicating progressive component wear. The hydraulic system operated within a temperature range of 70–80°C, with a maximum temperature of 95°C, accelerating oil degradation through viscosity changes and oxidation. The study concludes that oil replacement intervals and operating temperature significantly affect oil degradation and hydraulic system performance. Therefore, periodic oil condition monitoring is necessary to determine optimal oil replacement intervals and maintain hydraulic system efficiency.